Hydrogen storage properties of Mg–Nb@C nanocomposite: Effects of Nb nanocatalyst and carbon nanoconfinement. (24th February 2021) - Zhu, Chengxiang; Chen, Ming; Hu, Miaomiao; He, Donghui; Liu, Yijin; Liu, Tong
Abstract: The Mg–Nb@C nanocomposite has been synthesized by a reactive gas evaporation method to simultaneously achieve carbon nanoconfinement and add Nb nanocatalyst. The size of Mg particles is range from 14 to 26 nm with average size of 20 nm. The small Nb catalyst about 5 nm are decorated in Mg particles, and the proportion of Nb is about 8 wt%. The amorphous carbon layer with thickness of 2 nm is coated on the surface of Mg–Nb nanocomposite. The nanocomposite can absorb 6.4 wt% H2 and desorb 6.3 wt% H2 in 5 min at 673 K. At 573 K, it can also uptake 5.8 wt% H2 in 10 min and release 4.8 wt% H2 in 60 min. The E a for hydrogenation and dehydrogenation are reduced to 60.2 and 59.7 kJ mol −1, respectively. Carbon nanoconfinement and Nb nanocatalyst effectively improve the hydrogen sorption kinetic of Mg. Graphical abstract: Image 1 Highlights: Nb nanocatalysts about 5 nm are decorated on the Mg nanoparticles of 20 nm. Amorphous carbon layer with thickness of 2 nm is coated on the Mg–Nb nanocomposite. Mg–Nb@C nanocomposite can release 4.8 wt% H2 in 60 min at 573 K. The E a of Mg–Nb@C nanocomposite for hydrogen desorption reduces to 59.7 kJ mol −1 . Carbon nanoconfinement and Nb catalyst improve hydrogen storage properties of Mg.